The role of peer rejection in adolescent depression. - Platt, B; Cohen Kadosh, K; Lau, J (2013)
Adolescence is a period of major risk for depression, which is associated with negative personal, social, and educational outcomes. Yet, in comparison to adult models of depression, very little is known about the specific psychosocial stressors that contribute to adolescent depression, and whether these can be targeted by interventions. In this review, we consider the role of peer rejection. First, we present a comprehensive review of studies using innovative experimental paradigms to understand the role of peer rejection in adolescent depression. We show how reciprocal relationships between peer rejection and depressive symptoms across adolescence powerfully shape and maintain maladaptive trajectories. Second, we consider how cognitive biases and their neurobiological substrates may explain why some adolescents are more vulnerable to the effects of, and perhaps exposure to, peer rejection compared to others. Finally, we draw attention to emerging cognitive and functional magnetic resonance imaging-based neurofeedback training, which by modifying aspects of information processing may promote more adaptive responses to peer rejection. A better understanding of the mechanisms underlying adolescent depression may not only alleviate symptoms during a period of substantial developmental challenges, but may also reduce the burden of the disorder across the lifespan.